Respuesta :
Answer:
B) (-2,1)
Step-by-step explanation:
In order to find a solution to a system of equations, substitute the point's x and y values into both of the equations, solve, and see if it makes the equation true.
1) Let's try the point (-2,1). First, substitute its x and y values into the first equation, 3x - 3y = -9. Thus, substitute -2 for x and 1 for y in the equation and solve:
[tex]3x-3y = -9\\3(-2)-3(1) = -9\\-6 - 3 = -9 \\- 9 = -9[/tex]
-9 does equal -9, thus (-2, 1) makes the first equation true.
2) Now, do the same thing but with the second equation, 2x + y = -3. Again, substitute -2 for x and 1 for y and solve:
[tex]2x + y = -3\\2(-2) + (1) = -3\\-4 + 1 = -3\\-3 = -3[/tex]
-3 does equal -3, thus (-2, 1) makes the second equation true.
By substituting its values into both equations, we saw that it made both equations true. Thus, (-2,1) is the answer.